Clinical Manifestation and Outcomes of Thrombolytic and Consevative Therapy in Covid-19 Patients with ST-Segment Elevation Pattern: A Case Series - Raditya Rizki Muhammad; Nadya Anisah; Arief Bowo Kurniawan; Hairudi Hairudi (Cardiovascular and Cardiometabolic Journal, 2021)
COVID-19 pandemic has become a global issues, especially involving cardiovascular diseases. The management of COVID-19 patients with ST-Segment elevation in early pandemic era faces new challenges. Challenges can occur in term of patient’s delay and healthcare safety. This case series discussed clinical manifestations, examination findings, alternative strategies including thrombolytic and conservative therapy, and patients’ outcomes. Keywords: COVID-19, ST-segment Elevation, Thrombolytic